Sledging rations of the Falkland Islands Dependencies Survey, 1948–50 - Fuchs, V. E. (Polar Record, 1952)
During the last two decades the sledging ration used by British antarctic expedition has gradually been standardized and recent minor variations have had little effect on total calorie value. It may therefore be useful to record both the ration and the rationing system adopted by members of the Falkland Islands Dependencies Survey at Stonington Island, Graham Land, during the sledging seasons of 1948–50. The ration was in a direct line of descent from that used by the British Graham Land Expedition in 1934–37, and has been evolved for the use of dbg-sledge parties travelling long distances without air support or mechanical vehicles. It provides a balanced diet which has been found to keep a man in good health, as judged by body weight and ability to maintain continuous physical effort for long periods. It may be consumed at varying rates, but the party at Stonington Island always used it at the rate recorded below—27½ oz. per day. Although theration was satisfactory a general feeling of hunger made it necessary to maintain a personal mental discipline in eating neither more nor less than the allotted quantities of each item each day.